Diseño de interfaz usando minicomputador raspberry pi a ser usada en la impresión en 3 dimensiones, con demostración práctica de funcionamiento en prototipo de impresora reprap. - Ordoñez García, Jorge Enrique (2014)
This project presents the construction of an interface between a Raspberry Pi minicomputer, Arduino Mega board and a RepRap3D printer. The interface design is because these devices have different characteristics, being necessary the interconnection between these devices using their general-purpose GPIO ports of the Raspberry Pi board. It is also possible to use serial connection among these cards. To complete the interface it is necessary to enter certain commands on the Raspberry Pi under Linux operating system. Several programs must be installed to enable communication between these devices. Likethe Pronterface program that provides a graphical interface that allows the use of the Arduino IDE program to interact with stepper motors and an extruder, to be able to perform the required printing tests for the project.